Using Hyponymy Game to Improve Seventh-Grade Students’ Vocabulary Mastery at SMP Negeri 29 Makassar - Maharani, Srikandi Bulan; Sunra, La; G, Hasriani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The purpose of the research was to find out whether or not the use of hyponymy game improves students’ vocabulary mastery; meaning, spelling, pronunciation, word classes and word use. The researcher applied pre-experimental method. The population was seventh-grade students of SMP Negeri 29 Makassar in academic year 2023-2024 and the sample of this research were 29 students from class VII/1 by using cluster random sampling. The data were collected through test (pre-test and post-test). The result of data analysis stated that the mean score of pre-tests (58.06 with standard deviation 7.32) was lower than mean score of post-tests (88.00 with standard deviation 4.97) therefore the value of t-test (16.300 with significant difference 0.00) level of significance (α) = 0.05 and degree of freedom (df) = 28. It shows that the alternative hypothesis of this research is accepted. Based on the finding of this study, the researcher concluded that using hyponymy game improve students’ vocabulary mastery at the seventh-grade of SMP Negeri 29 Makassar. Keywords: Vocabulary mastery, hyponymy game.